The Place Of Systematic Approach In The Formation Of Methodological Principles Of Forensic Engineering And Technical Examinations - Bohdaniuk, Ihor (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2022)
he analysis of scientific works made it possible to come to the conclusion that the scholars have created a fundamental basis for the methodology of forensic examination which is the basis for the formation of the methodological foundations of forensic engineering and technical examination for its further theoretical and practical development. This research paper identifies the place of the system approach in the formation of general principles of the methodology of forensic engineering and technical examinations. It has been established that the methodology can be formulated as a philosophical doctrine on the system of proven principles, norms and methods of scientific and cognitive activity, about forms, structure and functions of scientific knowledge, which are used in solving specific (special) research issues. It is emphasized that three levels are distinguished in the structure of general scientific methods: empirical methods, logical methods and techniques, heuristic methods, a detailed description of the methods of each level is given, and successive stages of experimental research are formed. It has been established that methodology is an independent scientific direction that studies the process of carrying out scientific research, describes and analyzes the stages of research and studies a number of other issues. This article’s purpose is to determine the place of the system approach in the formation of the general principles of the methodology of conducting forensic engineering and technical examinations which will allow the expert to obtain scientifically based results for drawing up a reliable conclusion. Conclusions. It is determined that the system is a whole, complex, unity (integrity) that consists (combines) of many elements connected with each other in which the element is the smallest part of the whole, necessary for the description of the system which cannot be divided further. The unity of general scientific and philosophical levels of knowledge is the basis of the methodology of scientific and cognitive activity, about forms, structure and functions of scientific knowledge. The methodology is proposed to be understood first of all as the methodology of scientific knowledge which is a set of theoretical provisions on the principles of construction, forms and methods of scientific and cognitive activity, in addition, it can be considered as a certain system of fundamental ideas. It is proven that methodology is distinguished as a separate scientific direction that studies the process of carrying out scientific research, describes and analyzes the stages of research and studies a number of other issues.
Keywords: system; system approach; levels of knowledge; science; methodology; methods; techniques; forensic engineering and technical examinations; principles of the methodology of conducting forensic engineering and technical examinations